Peritoneal closure or non-closure in open appendectomy: a reality or a myth - Wilkinson, T. R. V.; Chauhan, Mahendra K.; Trivedi, Isha (International Surgery Journal, 2018)
Background: The objective of this study is to analyze the difference of outcome and complications in peritoneal closure versus non-closure in open appendicectomy. Methods: This was the prospective comparative study. 126 patients with the diagnosis of acute appendicitis undergoing open appendicectomy divided in two groups non-randomly. Group A: Open appendicectomy with closure of peritoneum (n=59) and Group B: Open appendicectomy with non-closure of peritoneum (n=67). Intra operative time and post-operative period for pain and complications like wound infections, hernia and duration of hospital stay were analyzed. Patients were shown ‘visual analogue scale’ on a daily basis and those who reported unbearable pain given additional analgesia. Results: Operative time, number of doses of analgesic required, wound infections and duration of hospital stay in both groups were compared. Difference in operative time between both the groups was found to be statistically significant (p< 0.0001). Conclusions: Non-closure of peritoneum in open appendicectomy is associated with lesser operative time, and shorter duration of hospital stay. Hence, it can be safely recommended.